Review on thermal lattice Monte Carlo analysis - Fiedler, Thomas (Studium Press LLC, 2010)
In this review chapter, we introduce the recently developed Lattice Monte Carlo method for addressing and solving phenomenologically-based thermal diffusion problems especially for composite and porous materials. We describe in detail the application of this method to calculate effective thermal diffusivities and to determine temperature profiles including conditions of temperature-dependent material properties and materials exhibiting a phase change. Where possible, results of the method are compared with results of exact or finite element methods. Excellent agreement is demonstrated.